Is microfinance a poverty breaker? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Financial services in Djibouti are getting much-needed working capital from a loan of US$ 3.6 million from the International Fund for Agricultural Development (IFAD), agreed with the government in February 2003. The project will mainly target...